2008
DOI: 10.3138/jvme.35.4.511
|View full text |Cite
|
Sign up to set email alerts
|

TigerPlace: Training Veterinarians about Animal Companionship for the Elderly

Abstract: Students learn more effectively when they are actively engaged in the learning process. Therefore, case studies have become increasingly popular as a way to teach students about a representative subject. This article discusses the benefits of case studies, with a primary focus on how case studies can help veterinary medical students learn about the human-animal bond. The discussion is particularly aimed at veterinary medicine instructors and discusses how case studies can be used and why they are important. Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…McGolgan and Schofield (2007) undertook an exploratory research project in which they concluded that companion animals can improve an older person's emotional and physical wellbeing. Recent studies listed at anthrozoology.org include a focus on pets as a conduit for social capital, as they play a key part in the creation of social networks (Wood et al , 2005) and innovation in the teaching of veterinary students through a case study on the importance of the bond between older people and animal companions (Johnson et al , 2008).…”
Section: Pets and Older Peoplementioning
confidence: 99%
“…McGolgan and Schofield (2007) undertook an exploratory research project in which they concluded that companion animals can improve an older person's emotional and physical wellbeing. Recent studies listed at anthrozoology.org include a focus on pets as a conduit for social capital, as they play a key part in the creation of social networks (Wood et al , 2005) and innovation in the teaching of veterinary students through a case study on the importance of the bond between older people and animal companions (Johnson et al , 2008).…”
Section: Pets and Older Peoplementioning
confidence: 99%